(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Polymer engineering was born in the world’s great research labs needing to make and understand new types of plastics, rubber, adhesives, fabrics and coatings. Due to their synergistic and hybrid properties derived from several components, polymer nano particle composite materials have attracted the interest of a number of researchers. Such materials have different mechanical, electrical, optical and thermal properties, whether in solution or in bulk. These changes were caused by the nano particle’s physical presence and the polymer’s contact with the particle and the dispersion state. One advantage of nano particles, as it tends to have polymer additives, is that charging requirements are quite small compared to traditional additives. Particles of micro size used as reinforcing agents scatter light, thus increasing light propagation and optical clarity. Efficient dispersion of nano particles combined with good interfacial adhesion of polymer particles prevents scattering and enables the exciting possibility of developing strong yet transparent films, coatings and membranes. Based on the scale at which the property is described as well as on its physical basis, polymer properties are commonly classified into several groups.